Os Sistemas Únicos como estratégia de coordenação federativa: reflexos da relação intergovernamental nas políticas públicas de saúde e educação do Estado de São Paulo - Oliveira, Vivian Satiro De [UNIFESP] (2020)
Recent studies on Brazilian federative model have led to a decrease in relevance of the state entity (in here, the concept of state is used as province). In the foreground, this feature is attributed to the federative architecture adopted since the Federal Constitution of 1988, which delegates to States an indistinct scope of action compared to the entities of the municipalities and the Union. In addition, there are coordination gaps in vertically implemented public policies, which does not support the necessary protagonism for states being effective in implementation of cooperative public policies at local level. Since the 1990s, public policy systems inaugurated a new arrangement for intergovernmental relationship, mainly in the formulation and implementation phases of social policies. In this context, this work aims, based on Federalism theory and on the experience of the State of São Paulo, to discuss the shared institutional aspects about cooperation in two distinct systems: the Unique Health System, certainly the most successful portrait of public policy system implemented in the country, and the National Education System, which, although not formally established, is a priority agenda of the educational sector for decades.